The microvariation of the Spanish perfect in three varieties - Paz González (Universitat Autònoma de Barcelona, 2019)
This study investigates the variability in the use of the Preterit canté (‘I sang’) and the Present Perfect he cantado (‘I have sung’) across three Spanish dialects: Peninsular (PEN), Peruvian (PER) and Argentinian (AR). For this purpose, we analyze the effect of type of context and temporal adverbials on the selection of these two forms. The corpus has been obtained through online questionnaires, comprising a total of thirty-two exercises that evaluate the use of the two verb forms in the following contexts: continuative, relevance of present, life experience, prehodiernal context and without temporal adverbs. The results of this research seek to contribute to the description of dialectal differences with respect to the use of the Preterit and the Present Perfect from both a quantitative and qualitative perspective.